Influence of fluid intake on soccer performance in a temperate environment - Owena, J. A.; Kehoea, S. J.; Olivera, S. J. (Journal of Sports Sciences, 2013)
The study aim was to examine the effect of fluid intake and dehydration on soccer-skill and high-intensity, intermittent-running performance after 90-minutes intermittent exercise (Loughborough Intermittent Shuttle Test). Thirteen semi-professional, men soccer-players completed, the 90-minute intermittent exercise on three fluid trials: prescribed fluid equal to sweat loss (1.65 ± 0.17 litres: Mean ± s), ad libitum fluid (0.85 ± 0.19 litres) and no fluid. After the intermittent exercise, dehydration was equivalent to 0.3 ± 0.1, 1.1 ± 0.2, 2.5 ± 0.4% body mass loss on the prescribed-fluid, ad libitum-fluid and no-fluid trials, respectively. Soccer-skill and high-intensity, intermittent-running performance, as assessed by the Loughborough Soccer Passing and Shooting Tests, and the Yo-Yo Intermittent Recovery Test, declined after the intermittent exercise compared with assessments made before. The decline in performance was however similar on all fluid trials (P > 0.34 for interactions and effect sizes were trivial or small). These effect sizes suggest larger fluid intakes had limited and inconsistent (both beneficial and detrimental) effects on performance. In conclusion the results suggest that fluid intake during 90-minutes of intermittent exercise and modest dehydration have limited and inconsistent effects on soccer passing and shooting skill or high-intensity, intermittent-running in a temperate environment.